Integrasi Nilai Akhlak Terhadap Program LiSA (Lihat Sampah Ambil) di SMP IT Insan Kamil Batusangkar - Iman Asroa BS; Yanti Mulia Roza (Universitas Muhammadiyah Jember, 2022)
This study examines the integration of moral values into the LiSA program at SMP IT Insan Kamill Batusangkar. The research was motivated by the existence of the LiSA program at SMP IT Insan Kamil Batusangkar and the low awareness of students towards the environment. The research question is how to integrate moral values into the LiSA program at SMP IT Insan Kamil Batusangkar? The research was conducted with a qualitative approach using the field study method. Data were collected by means of field observations, teacher and student interviews, and documentation of the LiSA program. Data were analyzed deductively and presented in a narrative manner to answer research questions. The results of the research are the integration of moral values into the LiSA program at SMP IT Insan Kamil Batusangkar in the form of moral education towards the environment as well as increasing student awareness and independence in protecting the environment.